Territorially Oriented Development in the New Cohesion Policy - Słupińska, Monika (Acta Universitatis Lodziensis. Folia Oeconomica, 2013)
Last twenty years is the period of the ongoing debate on regional policy paradigm shift in terms of its objectives, priorities, instruments, entities and geographical area of intervention. The changing challenges and developmental conditions, including the ongoing process of deepening and widening of the European integration process, make it necessary to change the model of cohesion policy. Cohesion policy implemented by the European Union in recent years, evolving from a model of redistributive policies, focusing on the transfer of funds to disadvantaged regions in the direction of policy towards the use of endogenous potential and specific individual territories. Policy oriented in this way is to contribute to a better use of the development potential of the entire European Union to create growth, jobs and cohesion. The rationale for the proposed by the European Commission, the shape of the new cohesion policy are the conclusions of a series of studies and analyzes (OECD legacy – a new paradigm of regional policy, the report F. Barca – place-based development). The purpose of this article is to draw attention to the changes in the model of EU cohesion policy, transforming the policy – increasingly – in the direction of policy towards territorial dimension.